2013
DOI: 10.1515/cclm-2013-0195
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of haemoglobinopathies: our experience of 523 cases

Abstract: Our PD procedure is successful and reliable, and is useful in high-risk areas characterised by molecular heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 94%
“…Analytical procedures for the PD of inherited diseases are very heterogeneous, and laboratories must be equipped with advanced technologies that include: 1) scanning procedures like DHPLC [17] or sequencing, because in more than half the diseases, mutations are scattered throughout the disease-gene [18] and procedures based on restricted panels of mutations have a low detection rate [19]; 2) quantitative PCR or CGH to reveal large gene rearrangements found in CF [19], HA [20], thalassaemia [14], DMD [15], spinocerebellar ataxia [21] and other diseases [22]. In addition, CGH can be used to analyse chromosomal alterations associated with gain or loss of DNA thereby becoming a complementary approach to karyotyping [23]; 3) Southern blot, long PCR or capillary electrophoresis to assess microsatellite expansion typically found in Huntington's disease [24], fragile X syndrome [25], Friedreich's ataxia [26], DM1 [15], and spinocerebellar ataxia [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations